The Study of Living Hadith of the Ancak Tradition in Wedoroklurak Village, Candi, Sidoarjo - Umi Hanik; Ibnu Hajar Ansori (Esensia: Jurnal Ilmu-Ilmu Ushuluddin, 2019)
This article is a study of the Ancak tradition in the Wedoroklurak village community of Candi District in Sidoarjo. The study conducted with the theory of Living Hadith. The results of the study concluded that the Ancak Tradition is an activity that arises out of gratitude to God for agricultural products harvested by the community. The thanks were then expressed in the form of alms-giving and sending prayers to the village’s founding figures. The activity was carried out at the grave of Mbah Nursinah Kik Graji Kendil Wesi as the leader of the six figures who opened the village at that time. The series of events began with Khatmil Qur’an, followed by spiritual sparks, prayers, and shared meals. Seeing from the perspective of the Hadith, motivational aspects supported by the Hadith associated with alms from the results of efforts, as narrated by al-Darimi, al- Nasa’i, Muslims, al-Tirmidhi, Ibn Majah and al-Bukhari. From the form of its activities, the Ancak tradition can return to the general nature of the propositions relating to the virtue of reading the Qur’an, graves pilgrimage, praying for ancestors, and blessings to eat together. Judging from the series of traditional activities, it seems that nothing violates religious law, so the claims of local people who call Ancak as a religious tradition can be accepted. Its sustainability needs to be maintained and preserved as local wisdom that can foster harmony and the spirit of cooperation, also to instill the value of religiosity that is rooted in society, especially the value of gratitude and alms-giving.